SKIZOFRENIA TOKOH UTAMA DALAM NOVEL FIGHT CLUB KARYA CHUCK PALAHNIUK (SEBUAH ANALISIS PSIKOLOGIS) - Yunus, Robert Andrew (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This study entitled â€œSchizophrenia of the Main Character in the Novel Fight Club by Chuck Palahniuk. A Psichological Approach.â€ The objective of this research is to identify, classify and to analyze the mental dissorder namely â€˜Schizophreniaâ€™ of the main character in the novel entitled Fight Club by Chuck Palahniuk. The study is based on Psikological approach generally, and specifically on â€˜Schizophreniaâ€™. â€˜Schizophreniaâ€™ of the main character then will be classified and categorized by its symptoms and causes. The writer is focusing on the main character with the extrinsic approach of analysis. Therefore, emphasizing on the identification of â€˜schizophreniaâ€™sâ€™ sympthoms as it is indicated on the main character, based on the diagnosis of international standard Diagnostic and Statistical Manual of Mental Disorders (2000), as well as identifying the determining factors of how the main character in the novel Fight Club related with the mental illness, namely â€˜Schizophreniaâ€™ based on a UK medical journal, The Lancet (2009). The result of this study shows how schizophrenia affects the main character in the novel Fight Club by Chuck Palahniuk. The result also shows the causes of schizophrenia found in the main character of Fight Club. Â  Keywords: Schizophrenia, the main character/the unnamed narrator, psychological analysis